Diabetic Retinopathy: Pathogenesis, Clinical Features and the Role of Physical Activity in Prevention and Management - Marzec, Wiktoria; Boral, Wiktoria; Dróżdż, Marek; Puliński, Jan; Linke, Julia; Napierała, Michał; Stupnicki, Szymon; Bajkacz, Agnieszka; Olkowski, Bartosz; Maczkowska, Alicja (Quality in Sport, 2026)
Background Diabetic retinopathy (DR) is a vision-threatening microvascular complication of diabetes mellitus that affects the retina and is classified into non-proliferative (NDPR) and proliferative (PDR) forms with diabetic macular edema (DME) representing an additional sight-threatening manifestation. Aim This study provides a comprehensive overview of diabetic retinopathy, integrating current knowledge of its pathogenesis, risk factors, clinical features, diagnostic methods, treatment options and potential impact of physical activity on disease prevention and progression. Material and methods This study was conducted as a review of the selected literature on diabetic retinopathy available in the PubMed database. Keywords included “Diabetic retinopathy”, “Nonproliferative diabetic retinopathy”, “Proliferative diabetic retinopathy”, “Glycemic control”, “ Physical activity”. Results Diabetic retinopathy can remain asymptomatic for long periods, making regular eye examinations essential for its early detection. Strict control of blood glucose and blood pressure helps prevent the onset and slow the progression of diabetic retinopathy with inflammation playing a central role in its pathogenesis. In addition, physical activity is associated with a reduced risk of DR with a particularly strong protective effect against vision-threatening diabetic retinopathy (VTDR). Current treatments include intravitreal corticosteroids, anti-VEGF agents, vitrectomy and laser photocoagulation. Early diagnosis combined with optimized management can significantly reduce the risk of permanent visual loss. Conclusion Diabetic retinopathy is a primary contributor to vision loss in working-age adults in developed countries. Growing insights into its pathogenesis and the discovery of new therapeutic targets offer promising opportunities for improved treatment.